ANALISIS MINAT MAHASISWA DALAM BERINVESTASI SAHAM PADA GALERI BURSA EFEK INDONESIA FAKULTAS EKONOMI UNIVERSITAS MADURA - Subhan, Subhan; Suryansyah, Ah (JURNAL AKUNTANSI DAN INVESTASI, 2019)
The Faculty of Economics is one of the faculties at Madura University that has an investment gallery. through this galerry, it will be a medium for Madura University student to invest shares in the capital market. the purpose of this study is to determine the effect of capital market education, minimal investment capitak, and return on student interest in investing in stocks.This type of research is quantitative associative. the data used are primary data obtained through the distribution of questionnaires to 275 respondent, namely 183 students of management study programs and 92 students of accounting study programs at the Faculty of Economics, University of Madura. the sampling method used by researches in each study program was proportionate stratified random sampling.The results of this study indicate that capital market education, minimal invesment capital and returns partially hhave a siginificant effect on students’ interest in investing in stocks.